TANGKI SEPTIK DAN PERESAPANNYA SEBAGAI SISTEM PEMBUANGAN AIR KOTOR DI PERMUKIMAN RUMAH TINGGAL KELUARGA - Sudarmadji Sudarmadji; Hamdi Hamdi (Politeknik Negeri Sriwijaya, 2013)
Every day, family residential neighborhoods discard the waste water that should be stored and processed. Most of waste water management system still does not meet the health requirements, it still use local waste water treatment systems (on-site) like septic tanks, because central wastewater treatment (sewage) is still not widely available in Indonesia. The local system does not require a huge cost when compared to a centralized system. Implementation and operation of the local system is more simply. Problems frequently encountered on the local system : the capacity and dimensions of septic tank does not fit requirements; effluent and influent not specification, there is no air pipes; channel infiltration does not performed percolation tests, the location of infiltration is too close with shallow wells; the slope of the bottom of the tank is not enough and only with one room at a time so that when suck the mud will be smelled. Need for septic tank construction planning, use of materials and determination of the true capacity of the septic tank. Also planning further treatment of septic tank with a leach field using channel permeation or infiltration wells. After calculation based Planning Procedures Septic Tank With Infiltration System SNI: 03-2398-2002 by way of calculation, capacity and dimensions are smaller than the septic tank by way of the table. After that, drawing plan should be made complete and detailed.